The Effect of Brand Image, Promotion and Servicesscape on Purchasing Decisions at Prima Freshmart Pekapuran Depok - Nadiah Pusparini; Jamaludin Khalid (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the effect of brand image, promotion and servicescape on purchasing decisions at Prima Freshmart Pekapuran Depok. Respondents in this study were Prima Freshmart Pekapuran Depok customers. The sampling technique in this study was purposive sampling. Respondents in this study amounted to 100 respondents. The method used is a quantitative method. While data processing in this study uses SPSS version 25. Based on the results of this study that brand image, promotion and servicecsape have a positive and significant effect on purchasing decisions at Prima Freshmart Pekapuran Depok.